Complex effects of international relations : intended and unintended consequences of human actions in the Middle East conflicts - Israeli, Ofer (Albany : State University of New York, 2020)
"Identifies the many ways in which unexpected outcomes are endemic to international relations due to the complexity of world politics"--
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Camp David Agreements -- (1978); Camp David Agreements (1978); International relations -- Decision making -- Case studies; Middle East -- Foreign relations -- 20th century; World politics -- 1945-1989.; Nuclear weapons -- Government policy -- Israel; Israel-Arab War, 1967.; Israel-Arab War, 1973.; Iran -- History -- Coup d'état, 1953.; Egypt -- History -- Intervention, 1956.; Relations internationales -- Prise de décision -- Études de cas; Politique mondiale -- 1945-1989.; Armes nucléaires -- Politique gouvernementale -- Israël.; Guerre israélo-arabe, 1967.; Guerre israélo-arabe, 1973.; Iran -- Histoire -- 1953 (Coup d'État); Égypte -- Histoire -- 1956 (Intervention étrangère); 1900 - 1999.; International relations -- Decision making; Nuclear weapons -- Government policy; World politics; Egypt; Iran; Israel; 1900-1999; Case studies; History